Diplazium esculentum (Retz.) Sw.: Ethnomedicinal, Phytochemical, and Pharmacological Overview of the Himalayan Ferns. (3rd September 2021) - Semwal, Prabhakar; Painuli, Sakshi; Painuli, Kartik M.; Antika, Gizem; Tumer, Tugba Boyunegmez; Thapliyal, Ashish; Setzer, William N.; Martorell, Miquel; Alshehri, Mohammed M.; Taheri, Yasaman; Daştan, Sevgi Durna; Ayatollahi, Seyed Abdulmajid; et al.
Abstract : The genus Diplazium (family: Athyriaceae) comprises approximately 350 species of pteridophytes . Diplazium esculentum (Retz.) Sw. is an important member of this genus and commonly known as a wild vegetable in the Himalayan and sub-Himalayan communities. According to the literature analysis, D. esculentum was traditionally used for the prevention or treatment of several diseases such as diabetes, smallpox, asthma, diarrhea, rheumatism, dysentery, headache, fever, wounds, pain, measles, hypertension, constipation, oligospermia, bone fracture, and glandular swellings. Various extracts of D. esculentum were evaluated to elucidate their phytochemical and pharmacological activities. A wide array of pharmacological properties such as antioxidant, antimicrobial, antidiabetic, immunomodulatory, CNS stimulant, and antianaphylactic activities have been recognized in different parts of D. esculentum . The review covers a systematic examination of pharmacognosy, phytochemistry, and pharmacological applications of D. esculentum, but scientifically, it is not fully assessed regarding complete therapeutic effects, toxicity, and safety in the human body. The published literature on D. esculentum and its therapeutic properties were collected from different search engines including Wiley online, PubMed, Springer Link, Scopus, Science Direct, Web of Science, Google Scholar, and ACS publications by using specific terms such as " Diplazium esculentum, bioactive compounds, biological activities and health benefits" from 1984 to 2021 (March). Therefore, further studies are required to identify the detailed action mechanism of D. esculentum in vitro/in vivo, and also, more studies should focus on conservation, cultivation, and sustainable utilization of the species.